Synthesis and Anesthetic Activity of Some Mannich Bases of p-Dimethylamino Benzylidene Acetanilide - Kalirajan, R.; Jubie, S.; Gowramma, B.; Suresh, B. (Asian Journal of Chemistry, 2010)
Some Mannich bases of p-dimethylamino benzylidineacetanilide are synthesized. The synthesized compounds havebeen characterized by IR and 1H NMR analysis. An attemptto determine the hydrophobic parameter (partition coefficient)is also established. All the test compounds have been screenedfor their local anaesthetic activity by Sollmann method.